Pension and Income on Local Areas of Russia: Differentiation and Affecting Factors; Innovation Management, Development Sustainability, and Competitive Economic Growth - Ryzhkova M. V. Marina Vyacheslavovna; Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Shinkeev M. L. Mikhail Leonidovich (2016, 2016)
Title screen